Math

posted by .

I solved the equation below and got an answer of 9+-sqrt(57) but i don;t belive this is correct. help please.

5-sqrt(8x+1)=x
8x+1=x^2-10x+25
0=x^2-10x+25-8x-1
0=x^2-18x+24
then i completed the sqare
got 9+-sqrt(57)

THANKS SO MUCH

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. MATH

    I need to simply this equation, but I got stuck. h/(4-sqrt(16+h)) = y First, I multiplied (4+sqrt(16+h)/(4+sqrt(16+h) to both sides, and I ended up with h(4+sqrt(16+h)/-h. Is this correct?
  2. Math(Roots)

    sqrt(24) *I don't really get this stuff.Can somebody please help me?
  3. math,correction

    i am really trying is this correct. solve: 5(x-2)^2 = 3 MY ANSWER THAT I GOT IS: X = 2 +- (SQRT (3) )/(5) no. 5(x-2)^2 = 3 (x-2)^2 = 3/5 x-2 = +- sqrt (3/5) x= 2 +- sqrt (3/5) so the whole fraction of 3/5 is inside the sqrt yes
  4. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  5. Calculus

    Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
  6. Math/Calculus

    Solve the initial-value problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else?
  7. Calculus

    Evaluate the indefinite integral: 8x-x^2. I got this but I the homework system says its wrong:sqrt((-x-8)x)/(2*sqrt(x-8)*sqrt(x))*(((sqrt(x-8)*(x-4)*sqrt(x))-32*log(sqrt(x-8)+sqrt(x))
  8. Math

    Can someone please check my answers below for accurateness?
  9. Calculus

    In these complex exponential problems, solve for x: 1)e^(i*pi) + 2e^(i*pi/4)=?
  10. 9th grade algebra (completing square)

    Can you check the following? A1. (2x + 3)^2 = 25 sqrt(2x + 3)^2 = +-sqrt(25) 2x + 3 = +- 5 2x + 3 = 5, 2x + 3 = -5 2x = 2, 2x = -8 x = 1, x = -4 {-4, 1} A2. x^2 + 14x + 45 = 0 x^2 + 14x + __ = -45 + __ x^2 + 14x + 49 = -45 + 49 (x

More Similar Questions